2010
DOI: 10.1093/nar/gkq1133
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anti-HIV-1 activity of G-quadruplexes comprising locked nucleic acids and intercalating nucleic acids

Abstract: Two G-quadruplex forming sequences, 5′-TGGGAG and the 17-mer sequence T30177, which exhibit anti-HIV-1 activity on cell lines, were modified using either locked nucleic acids (LNA) or via insertions of (R)-1-O-(pyren-1-ylmethyl)glycerol (intercalating nucleic acid, INA) or (R)-1-O-[4-(1-pyrenylethynyl)phenylmethyl]glycerol (twisted intercalating nucleic acid, TINA). Incorporation of LNA or INA/TINA monomers provide as much as 8-fold improvement of anti-HIV-1 activity. We demonstrate for the first time a detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 73 publications
(81 reference statements)
3
59
0
Order By: Relevance
“…Structural-activity relationship analysis showed that the presence of a DNA duplex and hydrophobic groups was crucial for the anti-HIV-1 activity observed, although the locations of the hydrophobic groups in the duplex and the sequence composition seemed not to be critical to the activity of the respective DNA duplexes tested. The modified DNA duplexes showed anti-HIV-1 activity at low M concentrations comparable to those of a previously described G-quadruplex HIV-1 entry inhibitor (17)(18)(19)(20)(21)(22)(23)(24). These duplex inhibitors were found to be interacting with the HIV-1 gp41 NHR deep pocket to prevent 6HB formation between the gp41 NHR and CHR.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Structural-activity relationship analysis showed that the presence of a DNA duplex and hydrophobic groups was crucial for the anti-HIV-1 activity observed, although the locations of the hydrophobic groups in the duplex and the sequence composition seemed not to be critical to the activity of the respective DNA duplexes tested. The modified DNA duplexes showed anti-HIV-1 activity at low M concentrations comparable to those of a previously described G-quadruplex HIV-1 entry inhibitor (17)(18)(19)(20)(21)(22)(23)(24). These duplex inhibitors were found to be interacting with the HIV-1 gp41 NHR deep pocket to prevent 6HB formation between the gp41 NHR and CHR.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast to Hotoda's quadruplex inhibitors d(TGGGAG) 4 (17)(18)(19)(20)(21)(22)(23)(24), the duplex inhibitors reported in this paper can be extensively modified based on the location of the hydrophobic groups and skeleton length, thereby presenting more opportunities for modification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T1 contained three hydrophobic groups (one TBDPS and two DMTs) at each end of the helix. The IC 50 for T1 was 1.8 -0.7 mM, comparable to the previously reported IC 50 values of duplex and quadruplex inhibitors [3][4][5][6][7][8][9][10][11][12][13][14][15]. T2 had no hydrophobic group modifications and did not show the anti-HIV-1 fusion activity.…”
Section: Odns and Triplexessupporting
confidence: 82%
“…Nearly 20 years ago, researchers discovered a category of DNA G-quadruplexbased inhibitors that display an anti-HIV-1 fusion activity [2]. Among these inhibitors, the most representative structure is Hotoda's sequence, d(TGGGAG), which interacts with the V3 loop or CD4-binding site of viral glycoprotein 120 (gp120) [3][4][5][6][7][8][9][10][11][12][13]. Recently, we designed a novel class of DNA duplex-based HIV-1 fusion inhibitors, which have hydrophobic groups at several selected positions [14,15].…”
Section: Introductionmentioning
confidence: 99%